PENGARUH TINGKAT LITERASI WARGA MUHAMMADIYAH TERHADAP INKLUSI KEUANGAN PRODUK TABUNGAN BANK SYARIAH - gultom, mitra sami; Afifah , Sarah (Ekonomi Islam, 2020)
The results of the Financial Services Authority (OJK) Survey in early 2018 showed that the level of Islamic financial literacy was only 8% while the level of inclusion, for Islamic banking itself, was at the highest literacy level, namely 6.6% literacy level and 9% level. 2016 shows that only 30 people have an adequate understanding of finance. This is a challenge to do to develop financial literacy. This study aims to see the level of literacy of Muhammadiyah citizens and financial inclusion of Islamic bank savings products. This research uses quantitative methods and simple regression analysis using SPSS Version 20 software. The independent variable in this study is Literacy. Finance (X1) from the results of the t-test of the financial literacy variable is 9,450 <0.1, which means a positive effect. And the F test shows jointly or simultaneously the Financial Literacy Variable on financial inclusion Sharia bank savings products with the calculated F value are 89,301 which means that it is greater than the F table, namely 3.95 and also has a significant value which is less than 0, 1 is worth 0.00. The test value of the determinant coefficient is 0.708. Keywords: Literacy Level, Muhammadiyah, Financial Inclusion, Savings Products